1972
DOI: 10.1113/jphysiol.1972.sp009945
|View full text |Cite
|
Sign up to set email alerts
|

Injections of calcium ions into spinal motoneurones

Abstract: SUMMARY1. In cats under Dial anaesthesia, Ca2+ was injected inside lumbosacral motoneurones, by passing currents between CaCl2-and KCl-containing barrels of compound micropipettes.2. There was a reduction in excitability and a fall in membrane resistance, both rapid in onset and quickly reversible. 4. The most common change in membrane potential was a hyperpolarization; but in nearly half the cases, there was no clear change or a small depolarization. A reversal level for the effect of Ca2+ could be measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…A Ca2+-induced K+ current is known to exist in various types of neurones (Meech, 1972(Meech, , 1974Krnjevi6 & Lisiewicz, 1972;Krnjevi6, Puil & Werman, 1975;Brown & Brown, 1973) and was suggested for the scallop photoreceptor . In those cases the conductance changes decay within at least several seconds, but it appears that the time course may depend on the experimental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A Ca2+-induced K+ current is known to exist in various types of neurones (Meech, 1972(Meech, , 1974Krnjevi6 & Lisiewicz, 1972;Krnjevi6, Puil & Werman, 1975;Brown & Brown, 1973) and was suggested for the scallop photoreceptor . In those cases the conductance changes decay within at least several seconds, but it appears that the time course may depend on the experimental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular injection of Ca 2+ into neurons of both invertebrates and vertebrates was subsequently found to activate a K + conductance (Krnjevi c and Lisiewicz, 1972;Meech, 1972). The discovery of a Drosophila mutant termed slowpoke (slo) (Elkins et al, 1986), in which a Ca 2+ -dependent component of K + current is lacking in indirect flight muscles, eventually led to the identification of the first gene that encodes a Ca 2+ -activated K + channel (Atkinson et al, 1991;Adelman et al, 1992) and its mammalian homolog (Butler et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol has been shown to decrease calcium entry via voltage-dependent channels (Lynch & Littleton, 1983) and also via voltageindependent channels (Stokes & Harris, 1982). On the other hand Baker & Shapira (1980) suggested that anaesthetics increased sensitivity of endogenous calcium binding proteins in the absence ofany alterations in intracellular calcium levels, while Krnjevic & Lisiewicz (1972) suggested that a rise in intracellular calcium activated calcium-sensitive forms of K+ and C1-permeability systems resulting in reduced 'Address for correspondence: Univ. Dept.…”
Section: Introductionmentioning
confidence: 99%